Nobility, virtue and magistratures in Claudius Mamertinus’ gratiarum actio to emperor Julian (Minerva, 2022)
The Gallic elite exclusion from the high positions of the Roman administration and its rise thanks to emperor Julian is an important milestone whose importance had been overlooked until now. Claudius Mamertinus was the first Gaul to achieve the consulate after a long period in which Rome had excluded Gauls from office. Mamertinus' consular speech in the light of this event seems to contain a vindication of the nobility originated in virtue against the corrupt nobility which, in Constantius II’s times, had monopolized the high magistratures. The speech is also a call for those honest men to collaborate with the new emperor.
Keywords: Panegyrici Latini; Claudius Mamertinus; Julian emperor; Gaul; consulship; nobilitas; Pliny the Younger